STRATEGI PEMBERDAYAAN MASYARAKAT LOKAL BERBASIS BAMBU DI KECAMATAN LOKSADO - Noor Rahmansyah; Mahrus Aryadi; Hamdani Fauzi (Lambung Mangkurat University-Indonesia, 2020)
Bamboo is a plant that can botanically be classified in the family Gramineae (grass). The economic and ecological benefits of bamboo, among other things, when compared to wood commodities, bamboo plants can provide an increase in the income of the surrounding community in a relatively fast time, which is 4-5 years. Demand that remains high is not followed by an increase in quality and prices that are compared to similar goods made from wood or other materials. This is a consideration and reduces the interest of the community to develop the business. This study aims to explore the understanding and role of community empowerment through the use of bamboo, explore the role of government in empowering bamboo-based communities and develop strategies for empowering local communities in the use of bamboo. This research is qualitative by using an emic approach that is focused on data and analysis based on answers from key people. The type of data consists of primary data obtained through interviews and observations. While the secondary data comes from the problem report documents that will be examined, writing and the results of research on the Local Community Empowerment Development Strategy. The results of this study indicate that the local community in Loksado District has the potential to develop processed bamboo production through community participation in bamboo processing and utilization training, the government and village apparatus support the processing and utilization of bamboo through programs / activities, cooperation, bamboo ecotourism and bamboo industrial products, and constraints in the empowerment of bamboo in Loksado District is in marketing and capital strategies.